2015
DOI: 10.1590/2176-9451.20.3.064-068.oar
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lower dental arch dimensions and tooth alignment in young adults without orthodontic treatment

Abstract: OBJECTIVE: The aim of this longitudinal study, comprising young adults without orthodontic treatment, was to assess spontaneous changes in lower dental arch alignment and dimensions. METHODS: Twenty pairs of dental casts of the lower arch, obtained at different time intervals, were compared. Dental casts obtained at T1 (mean age = 20.25) and T2 (mean age = 31.2) were compared by means of paired t-test (p < 0.05). RESULTS: There was significant reduction in arch dimensions: 0.43 mm for intercanine (p = 0.0089) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
6
1
1
Order By: Relevance
“…Especially in adult patients, as the intercanine distance tends to decrease, the altered position of canines becomes more pronounced. [16][17][18] Interestingly, mandibular premolars exhibited a lower discrepancy, as they are also the teeth with the smallest p-IPR. This indicated a general tendency for clinicians to concentrate IPR on the anterior region of mandibular teeth, especially on the incisors, although posterior IPR has been highly recommended by several studies as the enamel thickness increases in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Especially in adult patients, as the intercanine distance tends to decrease, the altered position of canines becomes more pronounced. [16][17][18] Interestingly, mandibular premolars exhibited a lower discrepancy, as they are also the teeth with the smallest p-IPR. This indicated a general tendency for clinicians to concentrate IPR on the anterior region of mandibular teeth, especially on the incisors, although posterior IPR has been highly recommended by several studies as the enamel thickness increases in this area.…”
Section: Discussionmentioning
confidence: 99%
“…The same tendency was observed in untreated patients, and it showed that this is associated with physiological processes or dental arch maturation. Natural aging processes also could affect the occlusion, and it could cause some overcrowding or changes in the dental arch dimensions [ 25 27 ]. Anyway, a long-term retention and regular checkups for any orthodontic patients are desirable because they could prevent a relapse in the lower front teeth and changes in the occlusion [ 24 , 25 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Berkurangnya lebar interkaninus dalam jumlah yang besar dapat menimbulkan bayangan gelap di daerah sudut mulut yang memperburuk penampilan. 11,13,14,15 Berdasarkan hasil penelitian Louly 12 , lebar interkaninus pada saat lahir sampai usia dua tahun bertambah 3,5 mm pada rahang bawah. Setelah usia dua tahun, lebar interkaninus terus bertambah pada rahang bawah sampai usia dua belas tahun.…”
Section: Pendahuluanunclassified